Socio-spatial polarisation and policy response: Perspectives for regional development in the Baltic States. (January 2022) - Lang, Thilo; Burneika, Donatas; Noorkõiv, Rivo; Plüschke-Altof, Bianka; Pociūtė-Sereikienė, Gintarė; Sechi, Guido
Based on a relational understanding of socio-spatial polarisation as a nested, multidimensional and multi-scalar process, the paper applies a comparative perspective on current trends of socio-spatial development in Estonia, Latvia and Lithuania. Comparing current scholarship and data on demographic and economic processes of centralisation and peripheralisation, we also examine political debates around issues of polarisation in different scholarly national perspectives. Despite variations in national discourses, our comparative perspective conveys strong similarities between the three Baltic countries in terms of socio-economic and demographic concentration in the capital regions to the disadvantage of the rest of the country. The analysis of regional policies further points to tensions between a concern for territorial cohesion on the one hand, and an adherence to the neo-liberal logic of growth and competitiveness against the backdrop of post-socialist transition on the other hand. An overview of case studies in the three countries shows a common reliance on endogenous resources to foster local development, conforming to the neo-liberal logics of regional policy. However, these strategies remain niche models with different levels of success for the respective regions and also among the populations in the region. As a result, we argue for a stronger role of regional policy in the Baltic countries that goes beyond the capital regions by better addressing the negative consequences of uneven development.